Diffusion of fluorescent molecules and quantum dot nanoparticles in viscous solvents investigated by fluorescence correlation spectroscopy. Issue 4 (28th August 2018) - Bao, Nguyen Thi Thanh; Van Trung, Dinh; Binh, Nguyen Thanh; Bich, Vu Thi; Thuy, Ung Thi Dieu; Phuong, Dang Tuyet
Abstract: The fluorescence correlation spectroscopy (FCS) is a powerful measurement technique allowing the study of dynamic properties of fluorescent molecules and nanoparticles in solution environment with high sensitivity down to single molecule/particle level. In this paper we investigate the diffusion of Rhodamine B molecules and fluorescent quantum dots in solvents with different viscosities using a FCS instrument. The measured correlation functions show that the diffusion times of all molecules and quantum dots increase with the solvent viscosity. From the experimental data we derive the diffusion coefficients and hydrodynamic radii of the dye molecules and nanoparticles in different solvents using the Stokes – Einstein relation. Our results show that the diffusion times depend linearly on the solvent viscosity while the hydrodynamic radii remain approximately constant. The results will be useful for further study of the dynamics of molecules and nanoparticles in various biological environments.